2018
DOI: 10.1016/j.breast.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity levels after treatment for breast cancer: Two-year follow-up

Abstract: Two years after breast cancer surgery, physical activity levels are still significantly lower compared to pre-operative values. Based on this limited recovery, it seems important to monitor physical activity levels in breast cancer patients and advice these patients to stay active after surgery and return to pre-operative activity levels in the long term as well. This study indicates the importance of long term monitoring and subsequently coaching of physical activity after breast cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 29 publications
3
38
0
6
Order By: Relevance
“…60--- 62 The results of this review showed that many patients only engaged in light-intensity activity following gynaecological cancer diagnosis and treatment. These results are consistent with previous studies in mixed cancer, 63 breast cancer 64,65 and colorectal cancer cohorts, 66 showing that cancer survivors significantly reduce their total, vigorous and moderate intensity PA 6 months and 1 year after diagnosis or treatment. The present review adds further evidence to demonstrate persistent low PA levels among patients following gynaecological cancer diagnosis and suggests that exercise recommendations for other cancer cohorts may also be applicable to this population.…”
Section: Discussionsupporting
confidence: 92%
“…60--- 62 The results of this review showed that many patients only engaged in light-intensity activity following gynaecological cancer diagnosis and treatment. These results are consistent with previous studies in mixed cancer, 63 breast cancer 64,65 and colorectal cancer cohorts, 66 showing that cancer survivors significantly reduce their total, vigorous and moderate intensity PA 6 months and 1 year after diagnosis or treatment. The present review adds further evidence to demonstrate persistent low PA levels among patients following gynaecological cancer diagnosis and suggests that exercise recommendations for other cancer cohorts may also be applicable to this population.…”
Section: Discussionsupporting
confidence: 92%
“…Despite recommendations of staying physically active after a cancer diagnosis, most patients with cancer and cancer survivors decrease PA level and struggle to meet PA recommendations [ 36 , 37 ]. In a longitudinal study conducted by De Groef et al [ 38 ], self-reported levels of activity were investigated among 267 patients with breast cancer before surgery and at several following time points. After 2 years, all activity levels (total, sports, occupational and household) were statistically significantly lower compared to preoperative levels [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal study conducted by De Groef et al [ 38 ], self-reported levels of activity were investigated among 267 patients with breast cancer before surgery and at several following time points. After 2 years, all activity levels (total, sports, occupational and household) were statistically significantly lower compared to preoperative levels [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is one of the top three cancers across the world with different treatment modes depending on the different subtypes (4). However, the current applicable treatment for BC exerts a considerable large and prolonged impact on the activity levels of BC survivors (20). This study aims to explore the potential regulatory role of hsa_circRPPH1_015 in the development of BC.…”
Section: Discussionmentioning
confidence: 99%